Echocardiography vs cardiac magnetic resonance imaging assessment of the systemic right ventricle for patients with d‐transposition of the great arteries status post atrial switch. (9th December 2019) - Samyn, Margaret M.; Yan, Ke; Masterson, Conor; Goot, Benjamin H.; Saudek, David; Lavoie, Julie; Kinney, Aaron; Krolikowski, Mary; Hor, Kan; Cohen, Scott
Abstract: Objective: Patients with Dextro‐transposition of the great arteries status post atrial switch (dTGA s/p atrial switch) are "at‐risk" for systemic right ventricular (RV) dysfunction. Due to complex RV geometry, echocardiography (Echo) does not allow accurate determination of ejection fraction (EF), but cardiac magnetic resonance imaging (CMR) allows quantitative right ventricular assessment. Measures of ventricular deformation may be precursors to global ventricular dysfunction. The primary aim of this study was to characterize imaging and clinical findings for adult patients with dTGA s/p atrial switch. Design: This was a retrospective cohort study of patients with dTGA s/p atrial switch operation (February 1966 to August 1988) with CMR performed at Children's Hospital of Wisconsin (from September 2005 to May 2015). Eligible patients had clinic visit, Echo, and exercise stress test within 1 year of CMR. Results: This study enrolled twenty‐seven patients (16 males, 11 females) with dTGA s/p atrial switch (18 with Mustard operation and 9 with Senning operation; median age 30 years; 74% New York Heart Association class 1 and 26% class 2). Seventy‐four percentage had normal RV systolic function (RV EF >45% by CMR). No correlation was observed between Echo strain data and clinical status (EF, exercise endurance, VO2 max, or New York Heart Association class). Cardiac magnetic resonance imaging RV global circumferential strain GCS and RV EF had moderate negative correlation ( r  = −0.65, P  < .001). Global circumferential strain was significantly different for those with RV EF above and below 45%, while global peak longitudinal strain (GLS) was not. Patients had reduced CMR myocardial strain values compared with healthy controls. Conclusions: Reduced RV CMR GCS (for those with RV EF <45%) suggests that CMR evaluation may enhance early detection of detrimental changes in the systemic RV myocardium.